New class of Zr precursor containing boratabenzene ligand enabling highly conformal wafer-scale zirconium dioxide thin films through atomic layer deposition - Ansari, Mohd Zahid; Janíček, Petr; Namgung, Sook; Kim, Hyangil; Nandi, Dip K; Cheon, Taehoon; Siddiqui, Masoom Raza; Imran, Muhammad; Jang, Yujin; Bae, Jong-Seong; Hong, Tae Eun; Park, Chaehyun; et al. (Elsevier Science BV, 2024)
This study presents the deposition of zirconium oxide (ZrO2) thin films through atomic layer deposition (ALD) using a novel Zr precursor, tris(dimethylamido) dimethylamidoboratabenzene zirconium [eta(6):eta(1)-(C5H5BNMe2)Zr(IV)(NMe2)(3)] and O2 reactant on SiO2/Si substrate in a range of 150-350 degrees C. The successful growth of highly conformal and amorphous ZrO2 films was possible using O2 as a mild oxygen source, which has rarely been found in ZrO2 ALD. This newly proposed process displayed distinct ALD characteristics, including self-limiting film growth and a linear relationship between the number of ALD cycles and film thickness, and exhibited enhanced deposition temperature window and growth per cycle of 0.87 Ang;, which is higher than those using several previously reported Zr precursors. Extremely conformal film growth with complete step coverage on trenches [aspect ratio of similar to 6.3] and uniformity on a 15 cm large SiO2/Si wafer was realized, which is one of the main highlights. Structural studies reveal a predominant amorphous nature of the as-deposited films and transition into nanocrystalline cubic ZrO2 films annealed at 850 degrees C with improved film properties such as stoichiometry, reduced impurities, which is confirmed by Rutherford backscattering spectrometry, X-ray diffraction, X-ray photoelectron spectroscopy, elastic recoil detection, and secondary ion mass spectrometry analyses. The optical properties of the prepared films were also examined via ellipsometry analysis.
Nové prekurzory Zr obsahující boratabenzenový ligand umožňující depozici vysoce konformních tenkých filmů oxidu zirkoničitého prostřednictvím depozice atomových vrstvev
Keywords: Atomic layer deposition; Novel precursor; ZrO2; Wafer-scale growth; Post annealing; Ellipsometry analysis; Depozice atomových vrstev; Nový prekurzor; ZrO2; Depozice na waferu; žíhání; Ellipsometrická analýza